Issues of Variance of Extreme Values in a Heterogeneous Teletraffic Environment (Global Journal of Science Frontier Research, 2015)
The reliability of various teletraffic data-analytical devices in communication systems is relevant to all stakeholders. Among other key external variables, the performance of the network evaluated under a variety of traffic scenarios is the focus of the study: data/video traffic generated by subscribers, who ordinarily subscribed voice bandwidth services. This study, therefore views teletraffic data as complete random and in-deterministic variables, and examines its continuous dependence on configuration of fixed engineering values by equipment innovators/operators. The study was carried out by examining if core equipment techniques for processing traffic data on real-time basis vary in accordance with the bandwidth required to deliver the service (voice, data and video). Four Line Trunk Groups (LTG01, LTG02, LTG03 and LTG04) and 16 Digital Line Units (DLUs) were used for the study. Close examination of the activated DLUs configured to carry voice bandwidth generated daily traffic values of 0.1Erlang to 0.2Erlang, while others generated traffic rates of 0.01Erlang to 0.05Erlang per line; during the non-busy-hour period. This traffic rates, though subscribed for voice services, were shared among voice, data and video. The study concludes that the time consistent busy hour is not truly consistent in the present heterogeneous traffic environment. New concepts were examined and recommendations made for review.
Keywords: average daily peak hour; busy hour; digital line unit; line trunk group; peak values; time consistent busy hour